Pterygia measurements are more accurate with anterior segment optical coherence tomography - A pilot study - Welch, MN; Reilly, CD; Kalwerisky, K; Johnson, A; Waller, SG (Nepalese Journal of Ophthalmology, 2011)
Introduction: Slit-lamp beam measurements of a pterygium can be difficult to reproduce accurately. Purpose: To compare standard slit-lamp beam measurements of pterygia to computer caliper measurements of Anterior Segment Optical Coherence Tomography (OCT) images. Subjects and methods: Thirteen pterygia of ten patients were evaluated. Two physicians independently measured each pterygium using the slit lamp beam. Caliper measurements of two different OCT images of each pterygium were obtained. All measurements determined the distance from the limbus to the pterygium apex. Results: The difference in the slit lamp beam measurements of each pterygium was calculated and the mean of the differences was 0.3 and the standard deviation was 0.32. The difference in the two OCT measurements of each pterygium was also calculated and the mean of the differences was 0.1 and the standard deviation was 0.12. A two-tailed t-test demonstrated a statistically significant difference in these measurements (p = 0.0256). Conclusion: Anterior Segment Optical Coherence Tomography (OCT) gives significantly more reproducible results than the slit lamp beam for measurements of the distance of a pterygium’s apex from the limbus. This tool may provide more accurate clinical assessment of extension of pterygia onto the cornea and may be useful for research purposes. Key words: pterygium; pterygia; anterior segment optical coherence tomography; OCT DOI: 10.3126/nepjoph.v3i1.4271Nepal J Ophthalmol 2011;3(5):9-12